2009
DOI: 10.3402/gha.v2i0.1839
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practice about malaria in rural Tigray, Ethiopia

Abstract: ObjectiveTo assess the knowledge, attitude and practice (KAP) regarding malaria and their determinants in a rural population of northern Ethiopia.MethodsThe study was conducted in the district of Samre Saharti, Tigray, northern Ethiopia. A structured questionnaire collecting socio-demographic and malaria-related KAP information was administered to the mothers from a representative sample of households.ResultsA total of 1652 questionnaires were available for analysis. Most of the respondents (92.7%) were able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
30
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 4 publications
16
30
6
Order By: Relevance
“…The majority of caregivers (77% 'at-risk' and 84% 'control' group) recognized that malaria is transmitted by mosquito bites, which is higher than the 5% and 48% observed in similar studies conducted in central and northern Ethiopia, respectively [31,32]. Moreover, mosquito bites as a cause of malaria were mentioned by more than half of the caregivers (both groups combined).…”
Section: Discussionmentioning
confidence: 78%
“…The majority of caregivers (77% 'at-risk' and 84% 'control' group) recognized that malaria is transmitted by mosquito bites, which is higher than the 5% and 48% observed in similar studies conducted in central and northern Ethiopia, respectively [31,32]. Moreover, mosquito bites as a cause of malaria were mentioned by more than half of the caregivers (both groups combined).…”
Section: Discussionmentioning
confidence: 78%
“…These studies have demonstrated communities' level of understandings and revealed some misconceptions related to signs and symptoms, mode of transmission, treatment or prevention of malaria. For instance, in a study from Tigray region, Ethiopia, mosquito as a cause of malaria was recognized by nearly half of the respondents (48.8%) [12]. In another study conducted among households in urban areas of Assosa zone, western Ethiopia, about 48% of study participants were aware that malaria can be transmitted by mosquito bites, and remarkable proportion of respondents had misconceptions regarding modes of malaria transmission [13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the long history of malaria eradication and control since the 1950s, malaria still a major public health problem in the country and main causes of hospitalization and death in all corners of the country (4). Malaria in Ethiopia is seasonal, predominantly unstable and focal, depending largely on rain fall and altitude.…”
Section: Introductionmentioning
confidence: 99%